Faktor – Faktor yang Memengaruhi Minat Nasabah Bank dalam Pemanfaatan Layanan Mobile Banking di PT Bank Syariah Indonesia KCP Medan Pulo Brayan - Hidayah, Nurul; Hamdani, Muhammad Faisal (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research aims to analyze and test the influence of information technology, usefulness and trust on customer interest in using mobile banking services at Bank Syariah Indonesia KCP Medan Pulo Brayan. The methodology used is a quantitative approach. The research subjects were 100 mobile banking users of Bank Syariah Indonesia KCP Medan Pulo Brayan. This research uses primary data collected through surveys. Data analysis in this research uses the SPSS software program to calculate validity, reliability, multiple regression, classical theory, f-test, t-test, and coefficient of determination. This research found that information technology, usability, and trust all have partial and simultaneous effects on customer interest in using mobile banking services at Bank Syariah Indonesia KCP Medan Pulo Brayan.